Promoting competition in the fertilizer industry in Africa: A global and local approach - Hernandez, Manuel A.; Torero, Máximo (International Food Policy Research Institute, 2018)
Given the central role that agriculture plays in the rural economy of Africa, several countries have implemented supply– and demand-driven policies and programs to promote sustainable fertilizer use, with mixed results. However, not much has been said about the market structure or competitive behavior along the supply chain in the highly concentrated fertilizer industry, nor about how this affects fertilizer uptake in the region. Globally, the industry has only a few producers, and African countries are highly and increasingly dependent on imported fertilizer. Locally, fertilizer distribution channels are also characterized by a limited number of market actors, often with a poor dealer network.